Infant behaviors and maternal parenting practices : short-term reliability assessments - Bornstein, Marc H. (2020)
Consistency in the order of individuals in a group across short periods of time-reliability-is both important developmentally and meaningful psychologically. For example, documenting the reliabilities of infant behaviors and maternal parenting practices elucidates the nature and structure of early development. In this prospective short-term longitudinal study (Ns = 51 5-month infants and their mothers), we examined reliabilities of individual variation in multiple infant behaviors (physical development, social interaction, exploration, nondistress vocalization, and distress communication) and maternal parenting practices (nurturing, encouragement of motor growth, social exchange, didactic interaction, provision of the material environment, and speech to infant). Medium to large effect size reliabilities characterize infant behaviors and maternal parenting practices, but both betray substantial amounts of unshared variance. Established reliability is essential to the application of these measures in infancy studies, it is central to replication, and it is a limiting factor in predictive validity.